Investigating Prospective Teachers' Mathematical Technology Understanding Within the TPACK Framework - Adirakasiwi, Alpha; Priatna, Nanang; Fatimah, Siti (UNNES JOURNAL, 2025)
Prospective teachers' understanding of the use of technology in mathematics learning through the TPACK framework. With technology becoming increasingly important in education, a strong understanding of TPACK is crucial for prospective teachers to design effective learning experiences. This study aims to investigate prospective teachers' understanding of the TPACK framework. This study is a qualitative research that used a single case design to investigate prospective teachers' understanding in the TPACK framework and involved teachers N=6 from mathematics education at Singaperbangsa University in Karawang. Three types of data were collected over 4 weeks, namely weekly observations, descriptions of progress reports, and lesson designs developed. The results of this study showed that most of the pre-service teachers had a limited understanding of technology integration in mathematics teaching. They tended to focus on the use of technology without paying attention to relevant mathematical contexts or effective pedagogical strategies. However, some pre-service teachers showed a better understanding of how technology can be used to support meaningful mathematics learning. The finding of this study is the need to develop training programs that strengthen pre-service teachers' TPACK skills, including integrated practical experiences and reflective learning on the use of technology in mathematics contexts. Through this research, it is expected that prospective teachers can deepen their understanding of how to integrate technology when they teach by considering aspects of content, pedagogy, and technology holistically in accordance with the TPACK Framework. The implication of this finding is the need for training programs in developing prospective teachers' TPACK competencies. Abstrak Pemahaman calon guru tentang penggunaan teknologi dalam pembelajaran matematika melalui kerangka TPACK. Dengan teknologi menjadi semakin penting dalam pendidikan. Pemahaman yang kuat tentang TPACK menjadi krusial bagi calon guru untuk merancang pengalaman belajar yang efektif. Penelitian ini bertujuan untuk menyelidiki pemahaman calon guru dalam kerangka TPACK. Penelitian ini merupakan penelitian kualitatif yang menggunakan desain kasus tunggal untuk menyelidiki pemahaman calon guru dalam kerangka TPACK dan melibatkan guru (N = 6) dari Pendidikan matematika di universitas singaperbangsa karawang. Tiga jenis data dikumpulkan selama 4 minggu, yaitu observasi mingguan, deskripsi laporan kemajuan, dan desain pembelajaran yang dikembangkan. Hasil dari penelitian ini menunjukkan bahwa sebagian besar calon guru memiliki pemahaman yang terbatas tentang integrasi teknologi dalam pengajaran matematika. Calon guru cenderung fokus pada penggunaan teknologi tanpa memperhatikan konteks matematika yang relevan atau strategi pedagogis yang efektif. Namun, beberapa calon guru menunjukkan pemahaman yang lebih baik tentang bagaimana teknologi dapat digunakan untuk mendukung pembelajaran matematika yang bermakna. Melalui penelitian ini, diharapkan calon guru dapat memperdalam pemahaman terkait bagaimana mengintegrasikan teknologi pada saat mereka mengajar dengan mempertimbangkan aspek konten, pedagogi, dan teknologi secara holistic sesuai dengan Framework TPACK. Implikasi dari temuan ini perlunya program pelatihan dalam mengembangkan kompetensi TPACK calon guru.